2022
DOI: 10.3390/su142114219
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Use of Aerial Scanning and Gis in the Design of Sustainable Agricultural Production Extension Works in an Agritourist Farm in Romania

Abstract: The use of scanning technologies and digital photogrammetry with the help of drones in the field of agritourism activities in Romania is a topic of novelty, because all the data necessary for the implementation or development of such research can be collected very quickly and with maximum efficiency. The classic methods are cumbersome and with a high consumption of inputs, and human and financial resources. The case study presents a practical method of applying this technology in the case of the agritourist fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------ Based on the calculated absolute coordinates of the points, the location and delimitation plan of the road was drawn up, using the AutoCad 2014 program, in dwg format (Kolbe, T. et al, 2011), at a scale of 1:500. The points were represented using the TopoLT application, from where the program was configured and the 1:500 scale was chosen (Figure 4) (Călina, J. et al, 2018). After reporting the coordinates (Figure 5), they were raised to the elevation of the land using the command: TopoLT -Transformation -Raise to the elevation of the points (Figure 6) (Raza, H., et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------ Based on the calculated absolute coordinates of the points, the location and delimitation plan of the road was drawn up, using the AutoCad 2014 program, in dwg format (Kolbe, T. et al, 2011), at a scale of 1:500. The points were represented using the TopoLT application, from where the program was configured and the 1:500 scale was chosen (Figure 4) (Călina, J. et al, 2018). After reporting the coordinates (Figure 5), they were raised to the elevation of the land using the command: TopoLT -Transformation -Raise to the elevation of the points (Figure 6) (Raza, H., et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In order to ensure the success of a photogrammetric project, it is imperative to know and manage both the available resources (equipment, qualified personnel, budget) [11] and the environment in which the activities will be carried out (weather conditions, flight restrictions, interferences, etc.) [7,12,13].…”
Section: Workflowmentioning
confidence: 99%
“…[7,12,13]. Starting from this principle, the workflow to be followed was established and the resources needed to achieve the objectives were estimated [11,14]. To carry out the case study, it was proposed to go through the work stages as shown in figure 3.…”
Section: Workflowmentioning
confidence: 99%